Cancer-Associated Fibroblasts in Pancreatic Cancer: Should They Be Deleted or Reeducated? - Qu, Chao (Integr Cancer Ther, 2018)
Pancreatic ductal adenocarcinoma is characterized by an extensive stromal response called desmoplasia. Within the tumor stroma, cancer-associated fibroblasts (CAFs) are the primary cell type. CAFs have been shown to play a role in pancreatic cancer progression; they secrete growth factors, inflammatory cytokines, and chemokines that stimulate signaling pathways in cancer cells and modulate the cancer biology toward increased aggressiveness. Therefore, targeting CAFs may serve as a powerful weapon against pancreatic cancer and improve therapeutic effects. However, a previous study aiming to deplete CAFs by inhibiting sonic Hedgehog signaling failed to show any benefit in survival time of pancreatic cancer patients. We reported that the natural product curcumin reeducated CAFs in pancreatic cancer treatment. A low concentration of curcumin reversed the activation of fibroblasts without exhibiting growth suppression effects. In addition, curcumin suppressed CAF-induced pancreatic cancer cell migration and invasion in vitro and lung metastasis in vivo. The results of our study suggest that active CAFs can be inactivated by certain natural products such as curcumin. Reeducation of CAFs back to their normal state, rather than their indiscriminate depletion, may broaden our view in the development of therapeutic options for the treatment of pancreatic cancer.